FACTORS ASSOCIATED WITH ADHERENCE TO ANTIRETROVIRAL THERAPY AMONG THE YOUTH RECEIVING LONG-TERM ART IN SELECTED HEALTH CENTRE IVS IN ISINGIRO DISTRICT, UGANDA - Kalega William; Otwine Tweheyo Anne; Jordan Amanyire (International Journal of Science and Research Archive, 2026)
Introduction: Optimal adherence to antiretroviral therapy (ART) is essential for viral suppression, yet the factors driving adherence among youth in rural Ugandan settings remain incompletely documented. This article, drawn from a wider study, examined the factors associated with ART adherence among youth receiving long-term ART in selected Health Centre IVs in Isingiro District, Uganda. Methods: A cross-sectional design employing a mixed-methods approach was used. Quantitative data were collected from 243 youths aged 18–30 years on ART using a structured questionnaire, while qualitative data were obtained from three counsellors and three peer educators through in-depth interviews. Bivariate ordinal logistic regression screened variables at p